Exogenous phasic alerting and spatial orienting in mild cognitive impairment compared to healthy ageing: Study outcome is related to target response. - Tales, A; Snowden, R; Phillips, M; Haworth, J; Porter, G; Wilcock, G; Bayer, A (2011)
Whether or not attentional mechanisms such as phasic alerting, spatial cueing and inhibition of return (IOR) remain intact in adults with Alzheimer's disease (AD) and mild cognitive impairment (MCI) remains a matter of debate. This is possibly the result of inter-study outcome variation caused by the adoption of different methodological components by different research groups. Here we investigated the influence of methodological factors upon study outcome, using a Posner-type exogenous cueing paradigm with amnestic MCI patients and healthy older controls. Specifically, we compared results when the required response involved target discrimination with results for a simple target detection response, using cue-to-target intervals (CTIs) of 200msec and 800msec in each case and with the same participants completing all conditions. For both groups, the presence or absence of both alerting and spatial cue-related effects depended upon the combination of target response requirement and CTI. Moreover, differences between the groups were specific to certain task conditions. The MCI group showed the same alerting effects as healthy people with a discrimination response, but the alerting effect shown by controls with a 200msec CTI and target detection was absent in MCI. Patients and controls showed similar spatial cue validity effects at 200msec CTI, but group differences emerged at 800msec CTI: target discrimination evoked a validity effect in the MCI group only, while target detection evoked an IOR effect in the healthy group only. These data indicate that detection and discrimination responses may each activate different attentional mechanisms, which are themselves differentially vulnerable in MCI. Thus a seemingly arbitrary choice of response may directly influence whether attentional processing appears preserved or disrupted in MCI. Furthermore, these data provide further evidence in support of the existence of significant visual attention-related functional abnormalities in amnestic MCI.